UPAYA PASTORAL KONSELING MENDALAMI DAN MEMFUNGSIKAN PERAN KASIH DALAM KELUARGA KRISTEN DI DESA BUHA, KECAMATAN TAGULANDANG SELATAN, SITARO - Samuel Manapode; Joshua Ronald Owen Wongkar (PT. Giat Konseling Nusantara, 2026)
Love is an essential element of life; it is an absolute certainty, for it is through love that the world continues to function in such harmony to this day. Christian families must be no different, where love must flourish, and the role of love must be prominently evident in the actions and attitudes of every member of the Christian family. This article aims to examine pastoral counseling efforts in exploring and applying the role of love in the lives of Christian families in Buha Village, South Tagulandang Subdistrict, Sitaro, using a qualitative ethnographic research method. This approach allows the author to deeply understand the reality of family life through cultural contexts specifically family culture as well as social relationships and practices of living out one’s faith. Data were collected through field observations, pastoral conversations, and reflections on experiences of family accompaniment in the daily life of the congregation. The findings indicate that the understanding of love within Christian families in Buha Village is quite good; however, there remains a need for “meaning-making” or the re-establishment of the role of love within some Christian families in Buha Village. Pastoral counseling efforts here mean that the counselor explores and accompanies families using various approaches, striving to nurture and bring to life the love that God has given and made present in every Christian family not merely understood, but effectively applied in tangible roles within the daily lives of Christian families in Buha Village.